Communication between cultures - Samovar, Larry A.; McDaniel, Edwin R.; Porter, Richard E. (Cengage Learning, 2017)
Packed with current research and examples, the 9th editions equips students with a deep understanding and appreciation of different cultures while helping them develop practical communication skills. Part I introduces the study of communication and culture; Part II focuses on the ability of culture to shape and modify our view of reality; Part III puts the theory of intercultural communication into practice; and Part IV converts knowledge into action. This is the only text to consistently emphasize religion and history as key variables in intercultural communication. Compelling examples force students to examine their own assumptions, perceptions, and cultural biases--enabling them to understand the subtle and profound ways culture affects communication. The ninth edition offers expanded discussions of the impact of globalization, a new chapter on intercultural communication competence, and more coverage of new technology.